Efforts to Prevent Musculoskeletal Disorders (MSDs) Among Staff at RSU Wahyu Medan Tembung District - Mutiara, Arifah; Harahap, Reni Agustina (PROMOTOR, 2024)
MSDs are the second largest contribution to disability in the world as the main cause that limits worker mobility and dexterity. Where they feel pain from the neck to the shoulders, then experience stiffness in the hand muscles until they lose control of their hands or find it difficult to move them. Complaints of Musculoskeletal Disorders (MSDs) are also felt as workloads for long periods of time at frequent intervals, repetitive work movements such as bending over while working, hunched sitting postures which make the staff particularly uncomfortable at work. to identify efforts to prevent MSDs in Wahyu RSU staff, Medan Tembung District. This research method uses qualitative methods using case studies. Samples were taken using the purposive method. The number of samples used in this research was 7 Wahyu RSU staff. The results of this research show that prevention efforts carried out by hospitals and each individual are still not effective in preventing the emergence of symptoms of MSDs in hospital staff. There needs to be more effort to prevent this by doing ergonomic exercises and stretching which must be done regularly. routine.